"Whistle for Willie," Lost Puppies, and Cartoon Dogs The Sociocultural Dimensions of Young Children's Composing, or Toward Unmelting Pedagogical Pots - Dyson, Anne Haas.; National Center for the Study of Writing and Literacy, Berkeley, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
No greater challenge currently faces the schools than articulating what a literacy curriculum for sociocultural diversity might look like. And yet the literature on young school children's composing has dealt only peripherally with this issue. In this theoretical essay, it is argued that, even for young children, the composing of both oral and written texts (i.e., planning, responding, revising) is a distinctly sociocultural process that involves making decisions, conscious or otherwise, about how one figures into the social world at any one point in time. Drawing on data from an ethnographic project in an urban school, the essay allows young children's composing processes sociocultural depth and breadth by highlighting variation in the kind of oral and written language genres a child uses, in the kinds of discourse traditions a child draws upon, and in the kind of relationships a child author enacts with others. The essay concludes with a discussion of the implications of a sociocultural perspective on young children's composing for literacy teaching and learning. One table and one figure are included. (Contains 72 references.) (Author/SR)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: R117G10036.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cultural Differences; Elementary School Students; Emergent Literacy; Literacy; Primary Education; Sociocultural Patterns; Writing Processes; Writing Research; Young Children; Childrens Writing -- Literacy as a Social Process; Opinion Papers; Reports, Research